2017
DOI: 10.3892/ol.2017.6823
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA PTENP1 inhibits proliferation and migration of breast cancer cells via AKT and MAPK signaling pathways

Abstract: We aimed to investigate the influence of long non-coding RNA (lncRNA) PTEN pseudogene-1 (PTENP1) on the proliferation, migration and cycle of breast cancer cells and its mechanism. Lentiviral vectors expressing PTENP1 were synthesized and breast cancer cells MCF7 were transfected with LV003-GFP-PTENP1 and LV003-GFP, respectively. The proliferation capacities of breast cancer cells were detected using CCK-8 assay, and the migration capacities of breast cancer cells were detected using scratch assay; flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…PTENP1 was reported as a tumor suppressor in development and progression of breast cancer. For instance, a recent study conducted by Tang et al (2017a) showed that PTENP1 suppressed proliferation and migration of breast cancer by inhibiting AKT and MAPK signaling pathways; another study performed by Gao et al (2019) demonstrated that PETNP1 increased expression of PTEN, thus mediating proliferation, invasion and drug resistance of breast cancer by activation of PI3K/AKT pathway. Connnexin 43 pseudogene, PsiCx43, increased sensitivity to cytotoxic chemotherapy of breast cancer (Bier et al, 2009).…”
Section: Breast Cancermentioning
confidence: 99%
“…PTENP1 was reported as a tumor suppressor in development and progression of breast cancer. For instance, a recent study conducted by Tang et al (2017a) showed that PTENP1 suppressed proliferation and migration of breast cancer by inhibiting AKT and MAPK signaling pathways; another study performed by Gao et al (2019) demonstrated that PETNP1 increased expression of PTEN, thus mediating proliferation, invasion and drug resistance of breast cancer by activation of PI3K/AKT pathway. Connnexin 43 pseudogene, PsiCx43, increased sensitivity to cytotoxic chemotherapy of breast cancer (Bier et al, 2009).…”
Section: Breast Cancermentioning
confidence: 99%
“…Its over-expression in MCF7 breast cancer cells has resulted in inhibition of cell proliferation and migration as well as down-regulation of cyclin A2, CDK2, p-AKT, p-p44/ 42 MAPK and p-p38 MAPK, so this lncRNA can impede the prol iferation and migration of breast cancer cells through modulation of AKT and MAPK signal ing pathways [64].…”
Section: Pten Pseudogene-1 (Ptenp1)mentioning
confidence: 99%
“…Thus, it is urgent to explore the novel therapeutic strategy to enhance tumor radiosensitivity for the treatment of PCa patients. Long non-coding RNAs (LncRNAs), as crucial modulators, participate in the initiation and development of many diseases, including cancers [3][4][5]. Urothelial cancer associated-1 (UCA1) was identified as an oncogene in various cancers [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (LncRNAs), as crucial modulators, participate in the initiation and development of many diseases, including cancers [ 3 5 ]. Urothelial cancer associated-1 (UCA1) was identified as an oncogene in various cancers [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%